Transparent bionanocomposite films based on chitosan and TEMPO-oxidized cellulose nanofibers with enhanced mechanical and barrier properties. (20th October 2016) - Soni, Bhawna; Hassan, El Barbary; Schilling, M. Wes; Mahmoud, Barakat
Highlights: Bionanocomposite films of TEMPO-oxidized cellulose nanofibers and chitosan were prepared. SEM and AFM images indicated that TEMPO-CNFs were completely embedded in the chitosan matrix. Nanocomposite films were less transparent and flexible than 100% chitosan films. Nanocomposite films possessed higher oxygen barrier properties than chitosan films. Nanocomposite films had higher thermal stability and mechanical properties than chitosan films. Abstract: The development of biobased active films for use in food packaging is increasing due to low cost, environmental appeal, renewability and availability. The objective of this research was to develop an effective and complete green approach for the production of bionanocomposite films with enhanced mechanical and barrier properties. This was accomplished by incorporating TEMPO-oxidized cellulose nanofibers (2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical) into a chitosan matrix. An aqueous suspension of chitosan (100–75 wt%), sorbitol (25 wt%) and TEMPO-oxidized cellulose nanofibers (TEMPO-CNFs, 0–25 wt%) were cast in an oven at 40 °C for 2–4 days. Films were preconditioned at 25 °C and 50% RH for characterization. The surface morphology of the films was revealed by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The thermal properties and crystal structure of the films were evaluated by thermogravimetric analysis (TGA-DTG) and X-ray diffraction (XRD). Incorporation of TEMPO-CNFs enhanced the mechanical strength of the films due to the high aspect ratio (3–20 nm width, and 10–100 nm length) of TEMPO-CNFs and strong interactions with the chitosan matrix. Oxygen and water vapor transmission rates for films that are prepared with chitosan and TEMPO-CNFs (15–25 wt%) were significantly reduced. Furthermore, these bionanocomposite films had good thermal stability. Use of TEMPO-CNFs in this method makes it possible to produce bionanocomposite films that are flexible, transparent, and thus have potential in food packaging applications.